X‐ray fluorescence determination of the manganese valence state and speciation in manganese ores. (7th April 2015) - Chubarov, Victor; Suvorova, Darya; Mukhetdinova, Anastasya; Finkelshtein, Alexander
<x xml:space="preserve">Abstract</x> This work concerns determination of the manganese valence state and speciation by wavelength‐dispersive X‐ray fluorescence analysis. The authors investigated the effect of the manganese valence state and speciation on the intensity of some К‐series lines of the X‐ray emission spectrum for the samples of manganese compounds. The intensities of MnKβ5 line and MnKβ′ satellite are least influenced by speciation, and they may be used for evaluating the manganese valence state for the samples containing low iron. The intensities of MnKβ″ and MnKβx satellites may be employed for assessing the manganese speciation. The results of X‐ray fluorescence determination of the manganese valence state and speciation in the manganese ores of the South Ural deposits agree with the X‐ray diffraction data. The X‐ray fluorescence method is definitely advantageous, because it does not require a complicated process of sample preparation and allows to receive fast information on the manganese valence state and speciation with the purpose to assess the quality of manganese ores. Copyright © 2015 John Wiley & Sons, Ltd.